What is social finance? Definitions by market participants, the EU taxonomy for sustainable activities, and implications for development policy - Sören Hilbrich (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
The market for social financial instruments is rapidly growing. The issuance of social bonds, for instance, reached 149.4 billion in 2020, showing an extraordinary growth of 720% compared to 2019 (ADB, 2021, p. 14). By providing capital for certain types of investments associated with positive social impacts, these instruments are intended to close funding gaps that hamper the realisation of social goals, as laid down, for instance, in the 2030 Agenda for Sustainable Development. In addition, social finance might set incentives for enterprises to engage in more sustainable business models that would give them access to social financial instruments potentially associated with a lower cost of capital. However, the magnitude of the potential contribution to society of social finance is a matter of debate. This paper focuses on an important challenge for social finance that concerns the plurality of existing definitions of social investments. The paper provides an overview of the definitions followed by market participants, describes the EU taxonomy for sustainable activities as a potential standard in this context, and discusses implications for development policy.
Keywords: 330